2023
DOI: 10.2196/40940
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Video Consultation for Preterm Neurodevelopmental Follow-up Care During the COVID-19 Pandemic: Cohort Study

Abstract: Background During the COVID-19 pandemic, parents of infants born very preterm or at risk were exceptionally worried about being infected. The only means of protection during the onset of the pandemic was social distancing. Video consultations for neurodevelopmental follow-up care were offered as an alternative way to stay in contact with patients and their families, to provide expert support, and to monitor and assess children’s development. Objective T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Self-assessment of their child empowered parents and gave them a better understanding of their child's neurodevelopment. They also addressed common screening questions and day-to-day concerns about weight gain, feeding, developmental milestones, and self-regulation (11,12). In line with these results According to Das et al, telemedicine is a viable tool for follow-up care (13).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Self-assessment of their child empowered parents and gave them a better understanding of their child's neurodevelopment. They also addressed common screening questions and day-to-day concerns about weight gain, feeding, developmental milestones, and self-regulation (11,12). In line with these results According to Das et al, telemedicine is a viable tool for follow-up care (13).…”
Section: Discussionmentioning
confidence: 75%
“…Video consultations were also feasible and showed some bene ts for parents in developmental neurological follow-up. Albayrak et al have shown that the neurodevelopmental status of an infant and a child is surprisingly easy to access (11,12). Self-assessment of their child empowered parents and gave them a better understanding of their child's neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11,15 Virtual visits may be more convenient for parents of infants who are medically fragile and require additional equipment such as oxygen. 16 For premature infants at increased risk of infection, having a virtual visit may help to limit their exposure to viral illnesses. 16 Importantly, provision of valuable therapies to high-risk infants was not delayed.…”
Section: Discussionmentioning
confidence: 99%
“… 16 For premature infants at increased risk of infection, having a virtual visit may help to limit their exposure to viral illnesses. 16 Importantly, provision of valuable therapies to high-risk infants was not delayed.…”
Section: Discussionmentioning
confidence: 99%